Chiny wyobrażone – Chiny ucieleśnione. Państwo Środka w polskich i serbskich relacjach z podróży (od XVIII do połowy XX wieku) - Galewska, Karolina (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article presents an overview of the issues discussed in Tomasz Ewertowski’s monograph Images of China in Polish and Serbian Travel Writings (1720–1949). It reconstructs the discourse that emerges from the journals as their authors report on their journeys to the Middle Kingdom. The article also analyses the conditioning of the presented attitudes in the context of individual experience. Using imagology-based tools, Ewertowski refers to the mental representations of reality recorded in the text in the form of stereotypically formed ethnotypes. Ewertowski creates a mosaic of the way travellers from the West imagined both Chinese cities and the characteristic features of Far Eastern culture, which is often marked by Eurocentrism and an evaluating attitude towards the Other.